HBsAg frequency in carriers applying to the public health laboratory - Edith Damaika (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Hepatitis B virus infections are one of the world's major health problems. Parenterally transmitted HBV can be found mainly in blood, but less frequently in bodily fluids such as saliva, semen, sweat, and tears, and transmission can occur percutaneously. For this reason, it is important to investigate HBsAg in public health carrier screening tests. Material and methods: In this study, HBsAg frequency microparticle ELISA (Vitros 3600, Ortho-Clinical Diagnostics) on serum samples taken to the Ministry of Health Afyonkarahisar Public Health Laboratory for screening porters of employees in the sector such as food, cleaning and tourism between September 2011 and March 2012. It was investigated by method. Samples with a positive reaction were verified by running the same kit a second time. Results and data were evaluated retrospectively. Results: Of a total of 1,961 porters, 311 (15.8%) women, between 18 and 65 years of age, were included in the study, 1,096 of the porters were eaten (56.0%), 312 were tourists, determined to be working in the cleaning (4.0%) sector and 470 (24.0%) of them were new hires. HBsAg positivity was found in 39 (1.9%) carriers, five of whom were women. It was determined that 32 (82.0%) of the HBsAg-positive porters were working in the food sector, 4 (10.3%) worked in the cleaning sector, and 3 (7.7%) were new hires. Conclusion: Most of the epidemiological studies on hepatitis B in our country show that intra-family or intra-community horizontal transmission of HBV in childhood and adolescence is at the forefront. In addition to parenteral applications, bodily fluids such as saliva, sweat, and tears are also prominent in horizontal community transmission. For this reason, monitoring for HBsAg in carrier screening is important in public health terms. (Journal of Viral Hepatitis 2012;18(1):57-9).